Josephson effect in point contacts between "f -wave" superconductors - Mahmoodi, R.; Kolesnichenko, Yu.A.; Shevchenko, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
A stationary Josephson effect in point contacts between triplet superconductors is analyzed theoretically for most probable models of the order parameter in UPt3 and Sr2RuO4. The consequence of misorientation of crystals in the superconducting banks on this effect is considered. We show that different models for the order parameter lead to quit different current-phase relations. For certain angles of misorientation a boundary between superconductors can generate a spontaneous current parallel to the surface. In a number of cases the state with a zero Josephson current and minimum of the free energy corresponds to a spontaneous phase difference. This phase difference depends on the misorientation angle and may possess any value. We conclude that experimental investigations of the current-phase relations of small junctions can be used for determination of the order parameter symmetry in the superconductors mentioned above.